2020
DOI: 10.1007/s00384-019-03490-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intraoperative indocyanine green fluorescence angiography on anastomotic leakage after laparoscopic sphincter-sparing surgery for malignant rectal tumors

Abstract: Whether indocyanine green fluorescence angiography (ICG-FA) during rectal surgery is effective in reducing anastomotic leakage remains unclear. This study aimed to investigate the effect of intraoperative ICG-FA on anastomotic leakage after sphincter-sparing surgery for malignant rectal tumors. MethodsThis was a retrospective, single-center cohort study conducted on 852 consecutive patients who underwent laparoscopic sphincter-sparing surgery from January 2007 to June 2017 at our institution. The incidence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 32 publications
1
40
0
Order By: Relevance
“…Our research identified 71 articles related to the use of ICG in vascular assessment of anastomoses, but only 23 papers remained eligible for review after a PRISMA evaluation [ 13 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. The ensuing comments and critical reflections are based on data from 3146 patients enrolled in 23 non-randomized studies on the use of ICG-enhanced NIR fluorescence for vascular evaluation of anastomoses in colorectal surgery involving open, laparoscopic, or robotic procedures ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our research identified 71 articles related to the use of ICG in vascular assessment of anastomoses, but only 23 papers remained eligible for review after a PRISMA evaluation [ 13 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. The ensuing comments and critical reflections are based on data from 3146 patients enrolled in 23 non-randomized studies on the use of ICG-enhanced NIR fluorescence for vascular evaluation of anastomoses in colorectal surgery involving open, laparoscopic, or robotic procedures ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some authors included all colorectal surgeries [ 13 , 17 , 25 , 29 , 32 , 34 , 35 , 36 ] for both benign and malign pathologies, as well as for all locations, while others focused on the most vulnerable colorectal segments with regard to blood supply, namely, the left colon and low colorectal anastomosis [ 19 , 20 , 21 , 22 , 23 , 24 , 26 , 27 , 28 , 30 , 31 , 32 , 33 , 37 , 38 ]. In 13 of the studies [ 12 , 15 , 17 , 18 , 19 , 21 , 22 , 23 , 24 , 29 , 30 , 33 , 34 ], only the group of patients receiving ICG was described, while in 10 studies [ 16 , 20 , 25 , 26 , 27 , 28 , 31 , 32 , 35 , 36 ], comparative lots of ICG and non-ICG patients were analyzed to evaluate the final outcome. In many cases, however, the control lots w...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the relationship between blood loss and AL, Hui Qu 36 conducted a meta‐analysis of seven retrospective and seven prospective trials evaluating risk factors for AL in patients with laparoscopic low anterior resection and reported that intraoperative transfusions/blood loss (>100 mL) was one of the risk factors for AL. Blood supply is necessary for wound healing at the anastomotic site, and the use of indocyanine green fluorescence imaging intraoperatively is effective in evaluating blood flow at the anastomotic site and also in reducing AL 37‐39 . Although the estimated blood loss in laparoscopic surgery is smaller than that in laparotomy, the relationship between blood supply at the anastomosis and blood loss is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Several comparative retrospective and prospective studies investigated the relationship between the use of ICG and the 30-d AL rate as the primary outcome[ 31 , 33 , 38 - 40 ]. They showed a statistically significant correlation between ICG FA and reduction in the risk of AL associated with the modification of the proximal section line.…”
Section: Assessment Of Vascular Perfusion At the Anastomotic Sitementioning
confidence: 99%